Research progress in farmland ecological effects and microbial degradation of quinclorac - SUN Yang; XU Huijuan; LI Xiaojing; LI Yongtao; ZHAO Lixia (浙江大学学报. 农业与生命科学版, 2017)
Quinclorac is one of the typical quinolinecarboxylic acid herbicides existing in farmland ecosystems. The research progress in effect of quinclorac on crops, community structure of soil microorganisms, enzyme activities and its degradation by microorganisms was reviewed comprehensively. The future works focusing on mechanisms of microbial degradation, screening of degradative bacteria, and application in farmlands were also proposed. The main contents are as follows: Quinclorac is relatively stable in the environment; quinclorac residues in soil can lead to changes of genes and functional enzymes in crops, thus causing damage to crops and resistance of some weeds; the presence of quinclorac in environment may cause animal dysplasia, metamorphosis and reproductive abnormality, thus affecting the diversity and abundance of animals; regular application rate has little effect on community structure of soil microorganisms and soil enzyme activities. Quinclorac often exists for a long time in natural environment, and the bioremediation based on microbial degradation is an effective way to control the quinclorac pollution. At present, researches on microbial degradation of quinclorac are conducted mainly in China, and several highly effective strains for degrading quinclorac isolated from contaminated soils and tobacco roots are mostly identified as bacteria. The degradation of quinclorac may attribute to the combination of decarboxylation reaction and dechlorination reaction. Temperature, humidity and pH are the main influencing factors of microbial degradation. Usually in a certain range, the degradation of quinclorac in soil accelerated with the increase of temperature and humidity. However, excessively high temperature or humidity would reduce the efficiency of microbial degradation. pH value mainly affected the microbial degradation of quinclorac in two aspects. Quinclorac is weak acidic and shows higher dissociation degree in slight alkaline soil, which is more easily degraded; on the other hand, the pH of soil has direct effect on the species and quantity of soil microbial communities, which has a great impact on the effect of microbial degradation. In conclusion, to reveal the complex physiological and biochemical processes and mechanism of soil microbial degradation, and explore the remediation technology for quinclorac contaminated soil, future work should focus on: 1) investigating the mechanism of quinclorac degradation at molecular biological level by the application of advanced molecular biological technology and tandem mass spectrometry technology, and constructing highly effective strains in degrading quinclorac through genetic engineering; 2) focusing on complex degradation of quinclorac by multiple strains; 3) verifying the effect of the currently isolated quinclorac-degrading strains in the field.